Assessment of hemodialysis adequacy and its relationship with individual and personal factors - Ozra Rezaiee; Nahid Shahgholian; Shahrzad Shahidi (Wolters Kluwer Medknow Publications, 2016)
Background: Hemodialysis is the most common renal replacement therapy in the world, and hemodialysis adequacy is an important and influencial factor in the reduction of various complications experienced by these patients. Multiple factors influence hemodialysis adequacy. This study was conducted to determine hemodialysis adequacy and its relationship with individual and personal factors in patients undergoing hemodialysis in three hemodialysis centers of Isfahan, Iran. Materials and Methods: This descriptive, cross-sectional study was conducted in partnership with 202 patients undergoing hemodialysis in three hemodialysis centers of Isfahan. The data were collected using a researcher-made questionnaire, and hemodialysis adequacy was measured using the urea reduction ratio (URR). Data analysis was conducted using Spearman's correlation coefficient, Mann-Whitney and Kruskal-Wallis tests, and descriptive statistics (frequency distribution). In this study, the level of significance was considered to be 0.05. Results: Hemodialysis adequacy in 56.4% of patients was optimal, in 29.7% near optimum, and in 13.9% less than optimal. Statistical tests showed a significant correlation between hemodialysis adequacy and age (P = 0.05), prehemodialysis systolic blood pressure (BP) (P = 0.02) and diastolic BP (P = 0.04), the duration of hemodialysis in months (P = 0.02), and patients' sex (P = 0.01). There was no significant correlation between hemodialysis adequacy and the number of hemodialysis cessations per week (P = 0.20), interdialytic weight gain (P = 0.40), prehemodialysis blood urea nitrogen (P = 0.40), creatinine (P = 0.10), hemoglobin (P = 0.20), hematocrit (P = 0.08), venous access type (P = 0.30), needle distance and direction (P = 0.70), underlying causes of end-stage renal disease (P = 0.50), and personnel's shift (P = 0.90). Conclusions: The results of the study showed that approximately half of the patients did not have an optimal level of hemodialysis adequacy, and multiple individual and personnel factors affect hemodialysis adequacy directly or conversely.